ANALISIS KEBIJAKAN PEMERINTAH DALAM PENANGANAN WABAH COVID-19 SEBAGAI KEBIJAKAN DARURAT MENURUT HUKUM TATA NEGARA DARURAT - Muhammad Mutawalli Awal; Tia Ludiana; Muhammad Nur Ichsan (JURNAL ILMIAH LIVING LAW, 2022)
This study aims to find out how the government implements policies in dealing with the Covid-19 outbreak as an emergency which is reviewed from the point of view of emergency constitutional law. In the study of emergency constitutional law, all forms of implementation of policies by the government were considered reasonable considering that the Covid-19 outbreak involved a state of emergency regarding health emergencies. The forms of government policies are considered to still have leniency in the implementation of policies to handle the Covid-19 outbreak, which has resulted in a very high number of positive cases and deaths in Indonesia. This type of research is normative legal research using legal material collection techniques through library research methods which are analyzed descriptively qualitatively. The results of this study are that by implementing a periodic lockdown program in each provincial area which is delegated to the regional government, it is able to reduce the number of positive cases and death rates from the impact of the Covid-19 pandemic outbreak. In the review of emergency constitutional law, government policies in handling Covid-19 are considered mandatory and legally allowed to be implemented, even though these policies override the applicable laws and regulations.